Indigenous people and their lands international stnadarts and domestic implementation the case of the Atlantic Coast of Nicaragua - Binder, Christina (España : Institute for human rights and humanitarian law, lund, sweden, 2002)
Trata de Indigenous people and their lands international stnadarts and domestic implementation the case of the Atlantic Coast of Nicaragua.
incluye índice
Keywords: 1. LEGAL CONCEPT OF PROPERTY 2. ENFORCEMENT